Avaliação de potência/teor de toxina botulínica tipo a por métodos cromatográficos e bioensaios - Xavier, Bruna (2018)
The botulinum toxin type A is one of the seven different serotypes of toxins produced by fermentation process with Clostridium botulinum, under anaerobic conditions. Biotechnological product has been used in therapeutic and cosmetic areas to inhibit the muscle hypercontraction and glandular hypersecretion. In the present study, it was developed and validated a size exclusion liquid chromatography (HPSEC) method to evaluate BoNTA in formulations of biopharmaceutical products. The analyses were performed on a TSKgel® G3000 SWXL column (300 mm x 7.8 mm i.d.) maintained at 25 ºC. The mobile phase consisted of 50 mM potassium phosphate, pH 7.0, run isocratically at a flow rate of 1.0 mL min-1 with photodiode array detection (PDA) set at 220 nm. The chromatographic separation was obtained with retention time of 13.5 min. The calibration curve was linear over the concentration range of 0.29 – 100 U mL-1 (r2 = 0.9998) and the limits of detection and quantitation were 0.08 and 0.29 U mL-1, respectively. The specificity was confirmed by forced degradation studies, interference of the excipients and peaks purity. The mean of accuracy was 100.41%, with bias lower than 0.93. The SE-LC method was applied to assess the content/potency and high-molecular-weight-proteins of BoNTA, and the results were compared with those of the reversed phase liquid chromatography (RP–LC) method previously validated, the T–47D cell culture in vitro bioassay and the mouse LD50 in vivo bioassay, giving mean values of content/potency of 0.87% higher, 0.36% lower and 0.71% higher, respectively. Aggregated forms showed significant decrease of the bioactivity and significant effects on the cytotoxicity (p < 0.05). In this context, the research of alternative methods according to the 3 Rs is emphasized and this study contributes to establish procedures to evaluate the quality, assuring the safety and therapeutic efficacy of biotechnological product.